Pengaruh Kepemimpinan Transformasional terhadap Organizational Citizenship Behavior yang Dimediasi oleh Kepercayaan Kepada Pimpinan: Studi pada Lembaga Perkreditan Desa Adat Jimbaran - Kadek Drasta Yoga Mahardika; I Gede Riana (Universitas 17 Agustus 1945 Semarang, 2025)
Voluntary actions of employees who contribute beyond their required roles are categorized as organizational citizenship behavior (OCB). OCB demonstrated by employees can drive the effectiveness of a company. This study aims to analyze the effect of transformational leadership on OCB mediated by trust in leaders at LPD Desa Adat Jimbaran. This study used a sample of 40 employees. The method used in this study was a survey method with questionnaire techniques and interviews with inferential path analysis statistical analysis tools. The results showed that transformational leadership had no significant effect on OCB. Trust in leaders had a positive and significant effect on OCB. Transformational leadership had a positive and significant effect on trust in leaders. Trust in leaders fully mediated the effect of transformational leadership on OCB. The implications of this study are to prove social exchange theory and its relationship to research variables. This study also offers the benefits of transformational leadership and trust in leaders on OCB.